Business Effectiveness of Online Reading Books (E-Books) in the Digital Era for Bina Mandiri University Gorontalo Students: Keefektifan Bisnis Buku Bacaan Online ( E-Book) Era Digital untuk Mahasiswa Universitas Bina Mandiri Gorontalo - Frezy Paputungan (LP2M Universitas Bina Mandiri Gorontalo, 2023)
Advances in technology require that changes are encouraged in human life from the information age to the digital era in all fields (Fitria, 2018). The use of technology as a learning medium is one of the innovative steps to improve the quality of education in Indonesia, so that it can compete at the global level. One form of student learning media that implements the development of technology and communication with user interaction that is currently being developed is a digital book, also known as an e-book (Hartanti, 2013). In the past, we could only read books in the form of sheets of paper arranged in such a way that the general public could read them. But now, along with the progress of the times, books are not only in paper form but can be in digital form that can be stored in a cellphone. A digital book or also called an e-book is a publication consisting of text, images, audio and published in digital form that can be read on computers or other electronic devices such as Android or tablets (Andikaningrum et al, 2014). The e-book itself makes the text and images in the form of digital media in either plain text format, pdf which can be opened with Acrobat Reader, or html format which can be opened by browsing or internet explorer offline. Even so, e-books still use the pdf format, because it is safer and more comfortable. The use of e-books is not intended to replace printed books, but e-books are designed to facilitate the reading process, make it more comfortable and can be used everywhere because of its small size, unlike conventional books which are large and thick. (Folb et al, 2011, in Hsio Chun-Hua et, al 2014). According to Gessner in Andi Murniati (2012), there are several advantages of publication in the form of electronic books, namely saving in production costs and fast in publishing and dissemination (speed-up in publication and dissemination). This is an advantage of online electronic publications in terms of economic factors, speed and very easy access. With the e-book, access to this application system can be used anytime and as often as possible, not limited to study hours and not depending on the place.